Towards high-throughput flim for protein-protein interaction screening of live cells and tissue microarrays - Barber, P; Pierce, G; Ameer-Beg, S; Matthews, DR; Carlin, L; Keppler, M; Kelleher, M; Festy, F; Gillett, C; Springall, R; Ng, T; Vojnovic, B; et al. (2008)
Studying cellular protein-protein interactions in situ requires a technique such as fluorescence resonance energy transfer (FRET) which is sensitive on the nanometer scale. Observing FRET is significantly simplified if the fluorescence lifetime of the donor can be monitored. Results from live cells and tissue micro arrays are presented from an automated microscope incorporating time-domain TCSPC fluorescence lifetime imaging (FLIM). Novel hardware and software with a modular approach and scripting abilities allow us to work towards speed-optimized acquisition and ease of use to bring FLIM into the high-throughput regime. ©2008 IEEE.